Smart Maritime Diplomacy: Diplomasi Maritim Indonesia Menuju Poros Maritim Dunia - Najamuddin Khairur Rijal (Global Strategis, 2019)
This article examines the efforts of Indonesia's maritime diplomacy, especially in Southeast Asia and ASEAN to realize the World Maritime Axis (WMA) vision. WMA is the “jargon” of the Joko Widodo government to realize Indonesia’s ideals as an advanced, independent, and strong maritime state, and has positive contribution to the world. Through a descriptive-qualitative research approach, to answer the efforts of Indonesian maritime diplomacy, the primary data was collected through a review of the annual reports of the Ministry of Foreign Affairs and the Ministry of Maritime Affairs and Fisheries. The secondary data is obtained through various literature related to WMA and Indonesian maritime diplomacy in Southeast Asia and ASEAN. By using Christian Le Miere's conceptualization of maritime diplomacy, this article shows that Indonesia’s maritime diplomacy efforts integrate the soft approach through cooperation and persuasive efforts with a hard approach through coercive action. By the author, this efforts is referred as Smart Maritime Diplomacy.